2022
DOI: 10.1111/eva.13489
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluating Coho salmon (Oncorhynchus kisutch) conservation units in Canada using genomic data

Abstract: Conservation units (CUs) are important tools for supporting the implementation of standardized management practices for exploited species. Following the adoption of the Wild Salmon Policy in Canada, CUs were defined for Pacific salmon based on characteristics related to ecotype, life history and genetic variation using microsatellite markers as indirect measures of local adaptation. Genomic data sets have the potential to improve the definition of CUs by reducing variance around estimates of population genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 133 publications
0
20
0
Order By: Relevance
“…Previous studies showed that this population is highly divergent from any others [35,36,52] and displayed an increased rate of long runs of homozygosity [38]. It has been subjected to extensive hatchery enhancement (from a single population) to circumvent the decline of Coho salmon in the Thompson drainage [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that this population is highly divergent from any others [35,36,52] and displayed an increased rate of long runs of homozygosity [38]. It has been subjected to extensive hatchery enhancement (from a single population) to circumvent the decline of Coho salmon in the Thompson drainage [53].…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that one population, the Salmon River (Thompson R. watershed) displayed an increased fixed load and decreased selection efficacy compared to southern populations. Previous studies showed that this population is highly divergent from any others [35,36,52] and displayed an increased rate of long runs of homozygosity [38]. It has been subjected to extensive hatchery enhancement (from a single population) to circumvent the decline of Coho salmon in the Thompson drainage [53].…”
Section: Discussionmentioning
confidence: 99%
“…The first condition for the protection of natural populations and their proper management is the identification of species’ genetic characteristics of their populations. Molecular markers such as mtDNA, microsatellites and MHC turned out to be sensitive enough to find a population differentiation generally congruent with the genomic methods based on the genotyping of a large number of SNPs in the conservation units of coho salmon ( Oncorhynchus kisutch ) in Canada [ 14 ]. However, the genotyping of many thousands of SNPs has revealed a more detailed structure in some evolutionary and biologically significant units.…”
Section: Conservation Geneticsmentioning
confidence: 99%
“…Despite stocking being carried out with material from a well-defined management unit, enhancement leads to a reduction in the diversity of this population compared to other wild populations. This is due to the reduction in the effective population size and the constraints of the gene pool representation [ 14 ]. Nevertheless, fisheries’ overexploitation of many declining populations is mitigated by stocking.…”
Section: Conservation Geneticsmentioning
confidence: 99%
See 1 more Smart Citation